Japan graphics 2 - Sakamoto, Tomoko (Barcelona, 2006)
The follow-up to international bestseller Japan Graphics, JPG2 examines changes in Japanese graphic design. Instead of 'more copies, higher resolution, to a wider audience', there is a greater focus on individual and original works. JPG 2 brings together over 20 design teams, showcasing the evolution of teams from the first JPG as well as new projects, new teams, and the best contemporary design talents. Works by Amane Murakami, Buddha Productions, Dainippon Type Organization, Enlightenment, Hideki Inaba, Higraph, keitarrow, Loworks, Keigo Mohri, Namaiki, Shinji Shimada, Ryuh Tomoaki, Sunday-Vision, Power Graphixx, Takora, Taku Anekawa, TGB design, Tsuyoshi Kusano, Tsuyoshi Hirooka, wabisabi, iseneehihinee.
Keywords: graphic design -- Japan; visual arts; Drawing. Design. Illustration; Commercial art. Advertising art